Differentiation and functioning of the lateral line organ in zebrafish require Smpx activity - Alberto Diana; Anna Ghilardi; Luca Del Giacco (Scientific Reports, 2024)
Abstract The small muscle protein, X-linked (SMPX) gene encodes a cytoskeleton-associated protein, highly expressed in the inner ear hair cells (HCs), possibly regulating auditory function. In the last decade, several mutations in SMPX have been associated with X-chromosomal progressive non syndromic hearing loss in humans and, in line with this, Smpx-deficient animal models, namely zebrafish and mouse, showed significant impairment of inner ear HCs development, maintenance, and functioning. In this work, we uncovered smpx expression in the neuromast mechanosensory HCs of both Anterior and Posterior Lateral Line (ALL and PLL, respectively) of zebrafish larvae and focused our attention on the PLL. Smpx was subcellularly localized throughout the cytoplasm of the HCs, as well as in their primary cilium. Loss-of-function experiments, via both morpholino-mediated gene knockdown and CRISPR/Cas9 F0 gene knockout, revealed that the lack of Smpx led to fewer properly differentiated and functional neuromasts, as well as to a smaller PLL primordium (PLLp), the latter also Smpx-positive. In addition, the kinocilia of Smpx-deficient neuromast HCs appeared structurally and numerically altered. Such phenotypes were associated with a significant reduction in the mechanotransduction activity of the neuromast HCs, in line with their positivity for Smpx. In summary, this work highlights the importance of Smpx in lateral line development and, specifically, in proper HCs differentiation and/or maintenance, and in the mechanotransduction process carried out by the neuromast HCs. Because lateral line HCs are both functionally and structurally analogous to the cochlear HCs, the neuromasts might represent an invaluable—and easily accessible—tool to dissect the role of Smpx in HCs development/functioning and shed light on the underlying mechanisms involved in hearing loss.